2020
DOI: 10.1111/1759-7714.13440
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of a gene signature in hiPSC associated with lung adenocarcinoma stem cells and its capability in eliciting specific antitumor immune‐response in a humanized mice model

Abstract: Background: Previous studies have reported that cancer stem cells (CSCs) play a key role in tumorigenesis, metastasis, and recurrence. CSC-based vaccination confers better protection in tumor cells. However, isolation and cultivation of CSCs are difficult. This study aimed to explore the similarities between CSCs and induced pluripotent stem cells (iPSCs). Methods: ALDH1+ cancer stem cells were isolated from lung adenocarcinoma patients and their gene expression patterns compared with human induced pluripotent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The concept of using embryonic stem cells (ESCs) or iPSCs as a prophylactic cancer vaccine has been evaluated in multiple studies in different murine tumor models, including models for lung cancer (Dong et al, 2010;Wang et al, 2020;Yaddanapudi et al, 2012), melanoma (Gąbka-Buszek et al, 2020Kooreman et al, 2018), ovarian cancer (Zhang et al, 2012), colon cancer (Li et al, 2009), and mesothelioma (Kooreman et al, 2018). These studies show the efficacy of ESC/iPSC-based cancer vaccines in preventing tumor development in mouse models in those cancer types and show the potential of these vaccines as promising prophylactic cancer vaccines, suggesting the need of testing these vaccines in more preclinical models and eventually clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of using embryonic stem cells (ESCs) or iPSCs as a prophylactic cancer vaccine has been evaluated in multiple studies in different murine tumor models, including models for lung cancer (Dong et al, 2010;Wang et al, 2020;Yaddanapudi et al, 2012), melanoma (Gąbka-Buszek et al, 2020Kooreman et al, 2018), ovarian cancer (Zhang et al, 2012), colon cancer (Li et al, 2009), and mesothelioma (Kooreman et al, 2018). These studies show the efficacy of ESC/iPSC-based cancer vaccines in preventing tumor development in mouse models in those cancer types and show the potential of these vaccines as promising prophylactic cancer vaccines, suggesting the need of testing these vaccines in more preclinical models and eventually clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The choice for these SMs was based on our previous observation that salicylic diamines can selectively induce apoptosis in leukemia and lymphoma cells and even overcome multidrug resistance 43 , 44 . Since PSCs share some characteristics with cancer stem cells 45 47 , we reasoned that these compounds might also exert selective toxicity against PSCs but not their differentiated derivatives.
Figure 1 Toxicity of small molecules SM1-SM16 against miPSC line aPIG-AT25.
…”
Section: Resultsmentioning
confidence: 99%
“…These results may suggest that the tumorigenic risk and immunogenicity of iPSCs can be utilized as advantages to generate iPSC-based cancer vaccines, which may exhibit potential usage as auxiliary therapy after surgery. Another parallel study demonstrated that iPSC had similar gene expression patterns with lung adenocarcinoma stem cells and could provoke anti-tumor immunity in humanized mice model [154]. Very recently, Gąbka-Buszek et al combined the whole-cell melanoma vaccine with stem cells, and demonstrated the increased effectiveness of the mixed cells in anti-tumor immunity.…”
Section: Possible Application Of Ipsc Technology In Developing Cancermentioning
confidence: 99%